Digitization, return, and circulation of sound recordings among the Bora in the Colombian Amazon - Maria Luísa Lucas (Journal de la Société des Américanistes)
This paper aims to present and discuss a case of return (or repatriation) of sound files among the Bora in the Colombian Amazon. Particular emphasis will be given to the ritual songs. Thus, we will examine how these song files have returned to their original places, as well as the access arrangements that affect them and how they are currently used. Such ethnographic data will reveal essential questions about the transmission of knowledge and the master-apprentice relationship. Following recent discussions on sound repatriation, I will discuss how new technologies can, on the one hand, rekindle relationships and help recover lost content but, on the other hand, might cause sickness and danger.